The Rise and Fall of Persegres: The Footprints of PT Petrokimia Gresik in the Dynamics of National Football Competition (1978 – 1996) - Muhammad Najib Khilmi; Sri Margana (Tarikhuna: Journal of History and History Education, 2025)
This study aims to examine the role of PT Petrokimia Gresik in the development of football in Gresik from the 1980s to the early 1990s, focusing on social support and the company’s Corporate Social Responsibility (CSR) strategies, as well as how sports were utilized as a social and promotional tool. Utilizing historical research methods and Bowen's CSR framework retrospectively, this study analyzes the internal and external factors influencing the trajectory of the Persegres team. The results indicate that PT Petrokimia Gresik's substantial investment in infrastructure and athlete development through the application of CSR principles successfully established Persegres as a prominent football power while simultaneously building a positive corporate image. However, the team subsequently experienced a decline and relegation in 1995-1996 due to changes in the competition structure, reduced financial support, internal conflicts, incidents of supporter violence, and match-fixing practices. It is concluded that the success and sustainability of a football team are highly dependent on consistent corporate support, robust internal management, and adaptation to external dynamics. This study provides an academic contribution by highlighting the complexity of interactions between CSR principles, sports development, and social dynamics within the context of industrial and community development.